Isolation and molecular characterization of Listeria spp. from animals, food and environmental samples - Atil, E.; Ertas, H. B.; Ozbey, G. (Czech Academy Agricultural Sciences, 2011)
A total of 46 Listeria spp. were isolated from 719 samples (milk, bulk tank swabs, cheese, feed, water, faeces and the environment) collected from 415 cattle and 304 sheep over 12 months (from February 2007 to January 2008). These isolates were identified by conventional and PCR techniques as belonging to L. monocytogenes (17.4%), to Listeria innocua (39.1%), to Listeria seeligeri 17.4%), to Listeria grayi (15.2%) and to Listeria welshimeri (11%). No Listeria ivanovii were isolated from any of the samples. Listeria spp. were not isolated from cheese and bulk tank swabs. With regard to seasonal variations most Listeria spp. were isolated in the spring and winter seasons. The eight L. monocytogenes isolates were characterized by PCR-RFLP with AluI and Tsp.509I. RFLP typing of the isolates revealed two different profiles with both restriction enzymes. Four and six different profiles were produced in the examination of L. monocytogenes isolates with RAPD analysis with HLWL74 and HLWL85 primers, respectively. This is the first report on the genotyping of L. monocyto genes isolates from various sources in Turkey. This study has highlighted the need for improved control and epidemiologic strategies to prevent the transmission of Listeria spp. to animals and humans.
Keywords: Listeria; seasonal variation; PCR-RFLP; RAPD